Positive and negative impact of word-of-mouth in the travel agency industry in Singapore. - Chew, Pei Yin. (2008)
This project explores the Word-of-Mouth behaviour in the travel agency industry in Singapore. It also looks into the number of repeat/lost customers and potential gain/lost customers.